Blue exorcist. 18 - Kato, Kazue, 1980-; Werry, John (Translator) (Shonen Jump advanced., 2018)
After dealing with the demons of Shura's past, Shura, Rin and Yukio return to True Cross Academy. While Yukio recovers from his wounds, Rin and his friends get back to their lives. But trouble is brewing as the Illuminati continue to advance their plans. Lightning launches an investigation of the Illuminati, intending to get to the bottom of things. With Suguro in tow, he delves into the archives deep below True Cross Academy, where he may uncover secrets that were buried there for a reason